Pengaruh Pemanasan terhadap Aktivitas Antioksidan pada Beberapa Jenis Sayuran - Yuliani Aisyah; Rasdiansyah Rasdiansyah; Muhaimin Muhaimin (Jurnal Teknologi dan Industri Pertanian Indonesia, 2014)
Vegetables is one of popular food for people in Indonesia. It is usually consumed in the form of fresh plant or after going through the process of cooking such as boiling, steaming and stirring-fry. Vegetable also contains many antioxidant components such as ascorbic acid, carotenoids, flavonoids, melanoidin, certain organic acids, reducing agents, peptides, tannin and tocopherol. Factor in this study is a type of vegetable and method of heating. Types of vegetable used i.e. S1 = Eggplant, S2 = Carrots, S3 = Broccoli and heating method comprising: P1 = without heating, P2 = boiling, P3 = steaming and P4 = stirring-fry. The results showed that the type of vegetable and methods of heating, as well as the interaction between the type of vegetable and method of heating gave very real effect on antioxidant activity. Effect of heating (boiling, steaming and stirring-airy) in some vegetables (eggplant, carrots and broccoli) gave different antioxidant activity.